Construction and Performance Characterization of Hexahydro-1,3,5-trinitro-1,3,5-triazine/Poly(3,4-ethylene-dioxythiophene)–Poly(styrenesulfonate) Energetic Composites - Zhiwei He; Gongzhen Zhang; Chuanhao Xu; Wenyu Zhu; Jiawei Yue; Shengtao Zhou; Zhenyi Huang (Molecules, 2025)
Hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX), a typical representative of energetic materials, is widely applied in military and industrial fields with its high energy density and excellent detonation performances. However, when used as a raw material for propellants and rocket propellants, RDX poses certain safety concerns due to its high sensitivity to external stimuli such as electrostatic discharge, impact, and friction, which limits its further application. Herein, to reduce the RDX electrostatic spark and mechanical sensitivities and improve safety performances, a conductive polymer of poly(3,4-ethylene-dioxythiophene)–poly(styrenesulfonate) (PEDOT:PSS) was introduced into the energetic material system based on a simple suction filtration method. RDX-based energetic composites with varying PEDOT:PSS mass fractions were prepared by both micron-sized RDX and nanosized RDX. The RDX-based energetic composites were characterized, and their response characteristics and performances were tested and compared. The results demonstrated that the conductive interfaces constructed by PEDOT:PSS on the RDX surface significantly reduced the electrostatic spark and mechanical sensitivity. The electrostatic spark sensitivity of μ-RDX-based energetic composites decreased by 40%, while the impact sensitivity and friction sensitivity decreased by 76.47% and 50%, respectively. Compared to micron-sized RDX-based energetic composites, the nano-sized RDX-based energetic composites desensitization effect on electrostatic spark sensitivity was more pronounced. For n-RDX-based energetic composites, the electrostatic spark sensitivity decreased by 66.4%. Furthermore, the assembly and desensitization mechanism of the RDX-based energetic composites were thoroughly investigated. This study not only provides a simple and reliable assembly method for the safe application of RDX but also offers corresponding data and experimental support for future research, which is of significant importance for the application of energetic materials.